A Conserved KIN17 Curved DNA-Binding Domain Protein Assembles with SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE7 to Adapt Arabidopsis Growth and Development to Limiting Copper Availability. Issue 2 (13th December 2013) - Garcia-Molina, Antoni; Xing, Shuping; Huijser, Peter
Abstract : An Arabidopsis homolog of KIN17 physically interacts with the transcription factor SPL7 to prevent impaired plant growth during periods of limited copper availability . Abstract: Proper copper (Cu ) homeostasis is required by living organisms to maintain essential cellular functions. In the model plant Arabidopsis ( Arabidopsis thaliana ), the SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE7 (SPL7) transcription factor participates in reprogramming global gene expression during Cu insufficiency in order to improve the metal uptake and prioritize its distribution to Cu proteins of major importance. As a consequence, spl7 null mutants show morphological and physiological disorders during Cu -limited growth, resulting in lower fresh weight, reduced root elongation, and chlorosis. On the other hand, the Arabidopsis KIN17 homolog belongs to a well-conserved family of essential eukaryotic nuclear proteins known to be stress activated and involved in DNA and possibly RNA metabolism in mammals. In the study presented here, we uncovered that Arabidopsis KIN17 participates in promoting the Cu deficiency response by means of a direct interaction with SPL7. Moreover, the double mutant kin17-1 spl7-2 displays an enhanced Cu -dependent phenotype involving growth arrest, oxidative stress, floral bud abortion, and pollen inviability. Taken together, the data presented here provide evidence for SPL7 and KIN17 protein interaction as a point of convergence in response to both Cu deficiency and oxidative stress.